[Hot Water Conduits to Reykjavik] - Streng, Evelyn Fiedler (1975)
Photograph of the hot water conduits to Reykjavik. The stone walls, the front white while the wall behind it grey and dirty, sit in parallel lines at the foot of a grass covered mountain in the background. A paved road curves along the left edge of the photograph, cars driving along it in the distance. Power line poles sit along the stone walls to the left.